IMPLEMENTASI AL-MAQASHID SYARIAH DALAM TATANAN HUKUM DI INDONESIA - Syapar Alim Siregar (Yayasan Baitul Hikmah al-Zain, 2024)
As a democratic country based on Pancasila, Indonesia must be able to defend the rights of its citizens in accordance with established standards. In Pancasila, religion has a sacred position in the legal order in Indonesia. So that these religious values have been included in the Indonesian constitution. This research is library research. The nature of this research is qualitative in accordance with the object of research study. The method used in this study uses a literature review, namely by collecting library materials including books, journals and others. Among the results of this research is that Indonesia has adopted the Maqashid Sharia system in many aspects of human life. Indonesia already has good regulations in Islamic banking, religious courts, child protection laws, violent sex crimes, drug laws, criminal laws, civil laws, and others. All of them aim to protect the religion, soul, spirit, property, and descendants of the Indonesian nation. This is in accordance with the values of the teachings of Islamic Shari'a.